Analysis of retrieval of dental implants displaced into ectopic locations between 2015-2017 and 2018-2020: scoping review of literature - Miyao Tadakazu; Osato Shigeo; Miyao Irika; Nakajima Yukari; Shirakawa Masayori (EDP Sciences, 2022)
Purpose: This study aimed to evaluate differences in 10 items of treatment details in patient regarding cases between 2015-2017 (EP) and 2018-2020 (LP) from scoping literature review of displaced dental implant (DDI) retrievals. Materials and methods: PubMed, Google Scholar, and ScienceDirect were searched using key words including "displaced," "retrieved," "migrated," or "accidental" dental implants. Treatment details were analyzed for the differences between EP and LP in 92 cases from 32 articles published in 13 countries. Statistical significance was evaluated using the Mann-Whitney U-test, Fisher's exact test, and Pearson's correlation analysis. Results: In the comparison between EP and LP, there was no significant difference in the number of publication countries (11 vs. 10), number of published articles (17 vs. 15), distributions of cases (50 vs. 42), mean age of patients (55.9 ± 1.8 years vs. 55.3 ± 2.5 years), male-female distribution (31/19 vs. 24/18), and distribution of displacement into the maxillary sinus and other regions (46/4 vs. 34/8), and no significant difference in the Pearson's correlation between publication years and the number of articles. DDI retrievals utilized intraoral and endoscopic surgeries (61.2% and 82.5%), transoral and transnasal approaches (93.8% and 81.8%), and local and general anesthesia (64.7% and 76.3%) during EP and LP, respectively. Moreover, significant differences were observed in all distributions between the two factors (30/19 vs. 7/33 cases, 30/2 vs. 6/27 cases and 2/12 vs. 9/29 cases) in EP and LP, respectively (P < 0.01). Conclusions: These results suggest that most DDI retrievals in otorhinolaryngology since 2018 have been mostly performed using transnasal endoscopic approaches under general anesthesia.